Ontogeny of consummatory successive negative contrast in rats - Suarez, Andrea Beatriz (2014)
Consummatory successive negative contrast (cSNC) occurs whenorganisms repeatedly exposed to a high-magnitude reward are suddenly given alow-magnitude reward. This results in a significant reduction in the consumption ofthe devalued reinforcer, at a level even below that of a group which had been alwaysexposed to the low-magnitude reinforcer. A scarcity of animal studies assessed theexpression of this phenomenon during early development. Three experimentsassessed age of cSNC onset in preweanling rats. Percent body weight gained(%BWG) and taste reactions associated with reinforcement devaluation weremeasured. A reduction in %BWG and a significant increase in emission of aversivehedonic behaviors, indicative of cSNC, occurred on postnatal day 18 (PD 18;Experiments 1 and 2), but not on PD 14 or PD 17 (Experiments 3a and 3b). Theneurobiological mechanisms underlying these effects and theoretical implicationsare discussed.